An Analysis of Figurative Language Used in the Song Lyrics of Four Twenty’s Album Lelaku - Dani, Riski Alpian; Nuriadi, Nuriadi; Isnaini, Muh (Edukasiana: Jurnal Inovasi Pendidikan, 2026)
This study examines the types and meanings of figurative language employed in the song lyrics of Four Twenty's Lelaku album within the context of Indonesian indie music. Employing a descriptive qualitative design, the study analysed all nine songs in the album as primary data sources. Data were collected through close reading and systematic documentation, then classified and interpreted using Kennedy's (1983) figurative language taxonomy supplemented by Nuriadi's (2016) formalist perspective. The analysis identified 38 instances of figurative language distributed across five types: personification (n = 14, 36.84%), metaphor (n = 11, 28.95%), simile (n = 7, 18.42%), metonymy (n = 4, 10.53%), and synecdoche (n = 2, 5.26%). Personification emerged as the dominant type, functioning primarily to animate abstract states, natural elements, and temporal phenomena as active agents in the speaker's emotional world — a pattern reflecting the contemplative and nature-connected aesthetic of Indonesian indie lyricism. The study further found that figurative type selection is systematically calibrated to each song's rhetorical register, as evidenced by the exclusive concentration of synecdoche in the album's single confrontational song. These findings contribute to an understanding of Indonesian indie music as a culturally distinctive and academically significant site of figurative creativity that extends and complicates Western-centred frameworks of figurative language analysis.